MANAJEMEN KOLABORATIF-DIDAKTIF DALAM PEMBERDAYAAN KOMUNITAS PENAMBANG PASIR DI LERENG GUNUNG MERAPI: STUDI PONDOK PESANTREN AL-QADIR, SLEMAN, YOGYAKARTA - Aris Risdiana; Fatimatus Zahro Jihan Fitri; Imam Nawawi (JURNAL MANAJEMEN DAKWAH, 2022)
This research examines Pondok Pesantren Al-Qadir, located in Wukirsari, Cangkringan, Sleman, Yogyakarta, which has been providing assistance to the sand miners' community in the slopes of Mount Merapi since the 2010 eruption. Data was collected through interviews, observations, and documentation, and then analyzed qualitatively and descriptively using a sociological approach. The findings of this study reveal that psychological trauma and economic devastation have pushed the community to their lowest point in life. However, KH. Masrur Ahmad from PP. Al-Qadir successfully addressed these challenges by organizing the eruption victims, providing spiritual support through mujahadahan rituals, creating job opportunities, establishing a wide economic network, and offering entrepreneurship education and an understanding of government regulations. The charismatic leadership of KH. Masrur, supported by the organic solidarity of the sand miners' community, enables the realization of a long-term economic empowerment vision through a collaborative-didactic management approach. Spiritual education and organizational development are also important focal points in these efforts.